MEDIASI KEPUASAN KERJA PADA HUBUNGAN ANTARA KOMPENSASI DENGAN PRODUKTIVITAS KERJA KARYAWAN - R Pandji Cepi Lesmana; Susi Widjajani (Fakultas Bisnis UKDW, 2015)
In General, this research aims to test the mediation of job satisfaction of the relationshipbetween compensation and employee productivity are divided into several formulationproblems. A sample of the object of research used a number of 123 people that come from theproduction field workers at PT BMB export. The results obtained were analyzed using pathanalysis method with the help of SPSS 20.1. the results showed that there is a positiverelationship between the compensation that is financially and non-financially towards jobsatisfaction and employee productivity and job satisfaction can be variable mediation of therelationship between financial and non financial compensation with employee productivityKeywords: Financial and Non Financial Compensation, Job Satisfaction, And EmployeeProductivity